INFORMATION SYSTEM DATA MANAGEMENT INCENTIVES EDUCATORS AND EDUCATORS AT PERMATA BANGSA KINDERGARTEN - Suryadi, Suryadi; Mola Ngaku, Anna Aldayuliani; Yohanah, Yohanah (Univesitas Muhammadiyah Tangerang, 2024)
The report on educator and educator incentive data that is currently running at TK Permata Bangsa is still done manually, namely collecting files and making data recaps for submitting lists of incentive recipients both education and educators are still recorded and made using Microsoft Excel. The collection of files and documents is done separately, this causes delays because it takes a long time. Teachers as educators and educators sometimes forget and are busy preparing the requested files. The research conducted seeks to provide solutions in processing data on educational incentives and educators, an application system that can be accessed easily. The information system created in the form of a web-based application will assist the school in making data reports on educational incentives and educators. The result of this study is in the form of an application that can be accessed through a browser. The research methodology used in the preparation of this thesis is direct interviews, observations and literature studies while the system development stage uses the Waterfall method. To design this application, a structural design method is used, namely Unified Modelling Language (UML).